Teachers' Understanding of Microsoft Office and Online Learning and Administration Support Applications at SDN Nanggewer Mekar Public Elementary School - Balqis, Tiara Ratu; Indupurnahayu, Indupurnahayu (Konsorsium Nasional Pengelola Jurnal Pengabdian, 2024)
The purpose of this study is to determine teachers' understanding of using technology to support the learning process and school administration during the Covid-19 pandemic. This research was conducted at SDN Nanggewer Mekar, a descriptive qualitative research method, with data collection techniques through observation, interviews, and questionnaires. The results showed that teachers who teach at SDN Nanggewer Mekar are mostly familiar with technology but have not maximized its use. With education and training, teachers can apply and maximize technology and overcome obstacles to the use of technology to develop learning processes by school learning programs